An In vitro Caco2‐Based Model for Measuring Intestinal Bioadhesion Comparable to Ex vivo Models - Eliyahu Drori; Valeria Rahamim; Dhaval Patel; Yamm Anker; Sivan Meir; Gal Uzan; Shira Somech; Chen Drori; Tal Tzadok; Aharon Azagury (Small Science)
This study presents an in vitro model using Caco‐2 cells that can mimic the bioadhesion properties of the human intestinal epithelium, aiming to reduce the use of animal tissues, in line with the 3Rs principle—replacement, reduction, and refinement. Specifically, a texture analyzer was used to assess the bioadhesive strength of hydrogels (i.e., alginate (Alg), chitosan (Chit), and gelatin (Gel)) under various applied forces (20–200 mN) and contact times (120–420 s). The results demonstrate that the in vitro model effectively predicts the bioadhesive strength of the tested hydrogels to ex vivo tissues (i.e., from mice, sheep, and pigs), including the effects of applied force and contact time. Also provided is an analysis of the effect of microvilli morphology on bioadhesion where an inverse relationship was observed between microvilli linear density and bioadhesion strength, explaining the variability in results across animal models. This Caco‐2‐based model offers a practical, accessible, and cost‐effective alternative to current ex vivo methods used for measuring bioadhesion fracture strength. It can be integrated into standardized testing protocols, providing a more ethical and scientifically robust approach to advancing bioadhesive drug delivery system research.